The Impact of Liquidity on Islamic Banks Profit: A Study on A Sample of Saudi Islamic Banks for the period 2013-2018 - Al-Akel, Haifa Saleh; Abdulrahman, Najla Ibrahim (Journal of Economic, Administrative and Legal Sciences, 2020)
This research aimed to study the effect of Liquidity on Saudi Islamic banks profitability, to achieve the goals of the research, the researcher has determined a sample of Saudi Islamic banks, the sample included Al-Rajhi, Al-Inma and Al-Bilad, the research focuses on the time period 2013-2018. The research used a descriptive methodology for the theoretical part by gathering previous studies, studies and scientific journals, for the applied part, the research used an analytical methodology by collecting financial statements of the study sample to use these data for hypothesis tests using statistical analytical methods, the results show that there is a statistically index effect on the index level (0.05) of the Liquidity ratio on the return of assets index in Saudi banks, they also show that the liquidity is inversely proportional to the return. The research recommended that Islamic banks should expand their services and attract depositors to take advantage with them in investment operations, This will make positive effects on their profits, in addition to that, Islamic banks administrations have to evaluate Liquidity risks continuously to deal with surplus and deficit.